A interatividade no ambiente virtual de aprendizagem MOODLE: a escola de gestores de educação básica da Paraíba - Sousa, Elizenda Sobreira Carvalho de (2010)
The present work has as its objective, analyze the interactivity between the course participants, teacher, content, platform, specifically the use of the synchronous and asynchronous interactive tools in the process of teach-learning of the Virtual Environment of Learning AVA (Moodle), in the 1st Course of Specialization in School Management of the Program of Pos-graduation in Education of the UFPB. As a contribution and theoretical base adopted for the accomplishment of this study, were considered the social representations of Serge Moscovici and the positioning and concepts about the interaction and interactivity of several authors that argue this theme on the virtual environment of learning. It was used as a instrument to collect data, the participant comment, the virtual semistructured interview and the questionnaire of research, all of this material send through the virtual tools (e-mail, forum, message box), to learn the social representation of the course participants about the interactivity lived in the course. Finishing, each time must qualify more the interactivity between all the actors of distance education, so that it gets better results in the process of teach and learn virtually.